DEIXIS ANALYSIS IN THE SHORT STORY THE WOMAN WHO LOST IN THE PATCHOUMI GARDEN - Ray, Sukma Adelina; Yulianda, Asri (LUMBUNG AKSARA, 2025)
This study analyzes the function of deixis (person, place, and time) in the short story "Perempuan yang Hilang di Kebun Nilam" by Helvy Tiana Rosa. Deixis, as a fundamental linguistic category that anchors discourse to context ("I, here, now"), is believed to be a key stylistic tool for constructing mystery and narrative perspective. This study uses a qualitative descriptive-pragmatic approach, with a close reading technique to identify, classify, and interpret deixis markers in the short story corpus. The results of the analysis show that deixis functionally creates a complex narrative structure, namely (1) Person deixis establishes the character Fauzan as (Narrative Subject), while the character “Woman” (Intan) is consistently placed as the Third Person Reference Object. (2) Place deixis (especially the phrase “in the Nilam Garden”) functions as a symbolic marker. The contrast between proximal (historical/emotional) and distal (physical/current) markers shows that the Nilam Garden is not just a setting, but a container of mystery. (3) Time deixis creates plot tension through double tense framing, comparing the present temporal (until now) with events of the distant past (two decades ago), forming a time hole that drives Fauzan’s search efforts. It is concluded that deixis in this short story functions as an efficient narrative tool in organizing space, time, and perspective to intensify the mysterious atmosphere and focus on the theme of loss.